Effects of Health Qigong Exercise on Lower Limb Motor Function in Parkinson's Disease - Li, Xiying; Lv, Chuanfen; Liu, Xiaolei; Qin, Xia (Frontiers in Medicine, 2022)
Purpose This study explored the effects of Health Qigong exercise on lower limb motor function in patients with Parkinson's disease (PD). Patients and Methods A total of 40 patients with PD were recruited and randomly allocated into the experimental group and the control group. The experimental group completed an intervention of Health Qigong exercise over 12 weeks, while the control group did not perform any regular physical activity. Data relating to gait, lower-limb joint range of motion, Timed Up and Go, as well as scores for motor function scale from the Unified Parkinson's Comprehensive Rating Scale III (UPCRS III) before and after the intervention were collected for Repeated Measure ANOVA. Results Compared to the control group, Health Qigong exercise improved the constant- and high-speed stride length and gait velocity of patients, but not constant- and high-speed stride frequency. Left and right hip flexion and extension range were improved as well as left and right knee flexion range. Finally, Timed Up and Go time became significantly slower and UPCRS III score significantly decreased. Conclusion Health Qigong exercise can improve walking ability and lower limb joint range of motion in patients with PD, lessen motor difficulties, and improve the quality of life. This non-pharmacological exercise intervention may be a useful adjustment treatment for PD.